Differences in Motivational Orientation in Physical Education in terms of Gender Differences - Arsani Arsani; Ali Maksum; Abdul Rahman SyamTuasikal; Nining Widyah Kusnanik (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
Motivation is one of the factors that influence the success of the physical education learning process. Motivation is divided into two dimensions, namely intrinsic motivation (arising from within) and extrinsic motivation (which is influenced by external or environmental factors). The success of physical education depends on the amount of motivation (motivation) that appears in students. If intrinsic motivation is greater than extrinsic motivation, the success of physical education will be easier to realize. This study aims to determine the motivation orientation of junior high school students in participating in physical education and to determine differences in motivation orientation based on gender in attending physical education in junior high schools. The population in this study were students of SMPN 40 Surabaya, amounting to 677 students. The research sample was 262 students. Sampling was done by random sampling technique with class as the unit of analysis. The data collection method in this study used a motivational questionnaire adapted from Deci (1971). This questionnaire has a validity of 0.356 to 0.755 and reliability (alpha) of 0.6854. To analyze the data, we used parametric statistical analysis of one sample t-test & independent samples t-test. To process it using the Windows version 20.00 SPSS statistical application program. The results obtained from the analysis of the one sample t-test as a whole obtained a mean value of 20.94 intrinsic motivation and a mean value of 14.63 extrinsic motivation. So that intrinsic motivation is greater than extrinsic motivation. For the results of the independent analysis of the sample t-test, it was obtained that F count was 3.68 with a significance of 0.00. Because it is significant 0.00 <0.05, the hypothesis is accepted. From the data analysis, it can be concluded that the motivation orientation of students of SMPN 40 Surabaya tends to be intrinsic and there are significant and significant differences in the motivation orientation between male students and female students based on gender differences.